2012
DOI: 10.1186/1748-717x-7-36
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated stereotactic radiotherapy for brain metastases larger than three centimeters

Abstract: BackgroundTo evaluate the efficacy and outcomes of hypofractionated stereotactic radiotherapy (HSRT) for brain metastases > 3 cm.MethodsFrom March 2003 to October 2009, 40 patients with brain metastases larger than 3 cm were treated by HSRT. HSRT was applied in 29 patients for primary treatment and in 11 patients for rescue. Single brain metastasis was detected in 21 patients. Whole brain radiotherapy was incorporated into HSRT in 10 patients for primary treatment. HSRT boosts were applied in 23 patients. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 21 publications
4
41
1
1
Order By: Relevance
“…Late radiation toxicity of 13.8% grade 3 cognitive impairment in our group was comparable to previous data of 6%-11% grade 3 late toxicities from other studies [16,17]. The incidence of radiation necrosis was one of the major concerns in late toxicities from WBRT plus focal radiotherapy boost, but it was quite infrequent in our study, and was similar to other reports of WBRT plus focal hfSRT boost [10,16-18]. Leukoencephalopathy and cognitive impairment were primary late toxicities in present study, and only history of EGFR-TKI treatment was a risk factor for grade 2 leukoencephalopathy in multivariate analysis, which had not been reported by other studies.…”
Section: Discussionsupporting
confidence: 91%
“…Late radiation toxicity of 13.8% grade 3 cognitive impairment in our group was comparable to previous data of 6%-11% grade 3 late toxicities from other studies [16,17]. The incidence of radiation necrosis was one of the major concerns in late toxicities from WBRT plus focal radiotherapy boost, but it was quite infrequent in our study, and was similar to other reports of WBRT plus focal hfSRT boost [10,16-18]. Leukoencephalopathy and cognitive impairment were primary late toxicities in present study, and only history of EGFR-TKI treatment was a risk factor for grade 2 leukoencephalopathy in multivariate analysis, which had not been reported by other studies.…”
Section: Discussionsupporting
confidence: 91%
“…Fractionated administration of radiation dose potentially decreases toxicity to late-responding normal tissues compared to a single acute dose of radiation for a given level of tumor damage [23], and reoxygenation and redistribution of the cell cycle between fractions render hypoxic tumor cells and cells in a lessresponding cell cycle more radiosensitive [9,16]. As expected from this concept, recently published studies on fractionated SRS for large BMs have demonstrated high LTC rates ranging from 63 to 100 % at 1 year with acceptable risks of toxicity [4,5,8,10,11,13,14,21,22]. Along with these, in the present study, the LTC rate was 87.0 % at 1 year and the median OS was 16 months in patients with large BMs treated with fractionated CK, which also compares well with the outcomes of single-fraction SRS for small BMs [6,17,26].…”
Section: Discussionmentioning
confidence: 86%
“…Recently, the concept of fractionated SRS has been emerging and is reportedly effective and safe in treating BMs, especially large ones [4,5,8,10,11,13,14,21,22]. The Cyberknife (CK) (Accuray, Sunnyvale, CA, USA) features a more flexible fractionation delivery of SRS compared with GK, as it relies on the frameless, image-guided technology for tracking the target both in space and time.…”
Section: Introductionmentioning
confidence: 99%
“…9 Using hypofractionated stereotactic radiotherapy, Jiang et al treated metastases up to 5.5 cm in diameter. 12 Nishizaki et al used multisession CyberKnife radiosurgery to treat brain metastases up to 53.2 cm 3 in volume.…”
Section: What Size Is "Too Big"?mentioning
confidence: 99%